2012
DOI: 10.1097/qad.0b013e328357f5ed
|View full text |Cite
|
Sign up to set email alerts
|

Risk factors for chronic kidney disease in a large cohort of HIV-1 infected individuals initiating antiretroviral therapy in routine care

Abstract: Objective To examine long-term effects of antiretroviral therapy (ART) on kidney function, we evaluated the incidence and risk factors for chronic kidney disease (CKD) among ART-naive, HIV-infected adults and compared changes in estimated glomerular filtration rates (eGFR) before and after starting ART. Methods Multicenter observational cohort study of patients with at least one serum creatinine measurement before and after initiating ART. Cox proportional hazard models, and marginal structure models examine… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
120
2
5

Year Published

2014
2014
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 116 publications
(131 citation statements)
references
References 48 publications
4
120
2
5
Order By: Relevance
“…We can also mention that the intensity of digestive disorders arising from the use of didanosine limit adequate hydration of patients which could lead to chronic kidney failure. In most studies, the molecules ARV most often associated with chronic kidney disease are tenofovir, indinavir, ritonavir and abacavir [7,25].…”
Section: Prevalence Of Chronic Kidney Failure In People With Hivmentioning
confidence: 99%
“…We can also mention that the intensity of digestive disorders arising from the use of didanosine limit adequate hydration of patients which could lead to chronic kidney failure. In most studies, the molecules ARV most often associated with chronic kidney disease are tenofovir, indinavir, ritonavir and abacavir [7,25].…”
Section: Prevalence Of Chronic Kidney Failure In People With Hivmentioning
confidence: 99%
“…Although individuals with two APOL1 high-risk alleles have a 4.25% lifetime risk of developing FSGS, those additionally infected with HIV have a 50% lifetime risk of developing HIVAN (6). Moreover, control of HIV infection with highly active antiretroviral therapy reduces the risk of CKD in patients with the APOL1 high-risk genotype (8)(9)(10). In another example, Divers et al (11) reported that the presence of JC viruria may be protective against kidney disease among individuals with two APOL1 high-risk alleles.…”
Section: Introductionmentioning
confidence: 99%
“…16 Another study documented a decreased CKD risk in association with CD4 cell restoration and plasma viral load suppression during treatment with HAART. 23 In our HIV population, the presence of albuminuria was the main factor associated with CKD (defined by the eGFR criterion). The presence of albuminuria is frequent and is observed in up to a third of patients infected with HIV.…”
mentioning
confidence: 99%